Implementación y evaluación de una herramienta distribuida de anonimización de capturas de red - Rigazio, Emilio (2010)
Nowadays, companies have computer networks feeding their operational systems, on these networks travels the invaluable information. In some cases that movement is the center of the business. Failures, delays, modifications or robbery can cause serious problems in the mentioned data movement. Due to mentioned log files contain the information that has traveled through the network in a certain period of time, they become delicate to handle because they may contain sensible information which represents security risks. This obstructs the analysis of these logs, because the organizations avoid the management of these archives, difficulting the possibility to generate best solutions to the problems networks present. It exists an anonymization process that consists in the pre-processing of log files in order for the sensible information they contain could be hidden. However, the processing becomes extensive because data that we probably are working with might be very heavy. This work is looking forward to resolve the problem set out during the distributed data processing, generating the possibility of the anonymization of a large amount of data in less time.